A SYSTEMS APPROACH TO THE STUDY OF COMMUNICATION ASPECTS OF ARCHITECTURE (Municipal economy of cities. Series: «Economy science», 2013)
Designation of the problems systematic approach to the study of the communicative aspect of the architecture in the present situation of scientific methods in the general theory of architecture. The possibilities of a systematic approach to develop the communicative perspective of architecture.